Determinants of non-farm entrepreneurial intentions in a transitional context: Evidence from rural Bulgaria - Diana Traikova (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2013)
Motivated by the regional imbalances and the long-lasting trends of low incomes, unemployment and depopulation in many of Europe's rural areas, this research delves into rural non-farm entrepreneurship as a potential way out. Up to now scholars from the field of entrepreneurial research have mostly investigated urban dwellers from developed economies. This work focuses on Bulgaria - a country, which recently underwent the difficult path of transition from a centralized to market economy. Although already a member of the European Union, it still struggles to overcome the connections mentality, inherited from communist times. Corrupt practices continue to shape the everyday economic choices and behavioural economics research should account for this aspect when trying to understand business creation. Making a step in this direction, this study seeks to identify the relevant factors influencing the formation of intentions to start a rural non-farm business. [...] – – Regionale Disparitäten, geringe Einkommen, Arbeitslosigkeit und der fortschreitende Bevölkerungsrückgang in vielen europäischen ländlichen Regionen sind die Motivation für diese Forschungsarbeit. Der Fokus dieser Studie richtet sich auf ländliches Unternehmertum als möglichen Ausweg aus den genannten sozioökonomischen Problemen. Bis jetzt hat sich die Forschung im Bereich des Unternehmertums hauptsächlich auf städtische Einwohner entwickelter Länder konzentriert. Die vorliegende Dissertation beschäftigt sich dagegen mit dem ländlichen Raum in Bulgarien - einem Land, das den schwierigen Weg der Transition von Planwirtschaft zu Marktwirtschaft gegangen ist. Es ist mittlerweile Vollmitglied der Europäischen Union, hat aber immer noch mit einer ausgeprägten Mentalität der Vetternwirtschaft und Korruption zu kämpfen. Sie bedingt, dass die meisten ökonomischen Entscheidungen durch Korruptionspraktiken begleitet werden und ist ein Erbe aus kommunistischen Zeiten. Wenn die Verhaltensökonomik die Gründung von Unternehmen verstehen will, sollte dieser Aspekt nicht vernachlässigt werden. Die vorliegende Studie macht einen Schritt in diese Richtung, indem sie sich auf die Suche nach den Bestimmungsfaktoren der Gründung außerlandwirtschaftlicher Kleinunternehmen im ländlichen Raum Bulgariens macht. [...]
urn:nbn:de:gbv:3:2-26914
Keywords: 330